Aktivitas Fan Labor dalam Fenomena Shipping Culture di Media Sosial X - Budi, Clarisa Oktaviani; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The phenomenon of shipping culture on social media is a result of participatory culture. This phenomenon allows shippers to create their own content without being confined to original content. Shipping culture is studied because of negative societal stigma and prejudice against the practice. Using qualitative descriptive research methodology through in-depth interviews with six informants, digital observation, and content documentation, this research explores how fan labor in the shipping culture phenomenon manifests in three main forms: specialized labor (AU and fanfiction production), managerial labor (community event management), and unskilled labor (voting and streaming campaigns). The research demonstrates that platform X facilitates shippers to actively participate in participatory culture, mobilizing thousands of followers to undertake collective actions that have tangible economic impact on idols' careers. The @kalewrittings account represents good fan labor practices by combining creativity with authentic support for idols. However, the research also identifies complexities within Indonesian shipping culture, including fetishization phenomena and the importance of boundaries between fantasy and reality. This research provides an evidence-based framework for understanding how fan labor in shipping culture can be managed ethically and sustainably without harming idols. Fenomena shipping culture di media sosial merupakan hasil dari budaya partisipatori. Fenomena ini mengizinkan para shipper untuk membuat konten sendiri tanpa harus berpatok dengan konten orisinil. Shipping culture diteliti karena stigma masyarakat yang beranggapan negatif dengan shipping culture. Dengan menggunakan metodologi penelitian kualitatif deskriptif melalui wawancara mendalam, observasi digital, dan dokumentasi konten, penelitian mengeksplorasi bagaimana fan labor pada fenomena shipping culture terbentuk dalam tiga bentuk utama: specialized labor (produksi AU dan fanfiction), managerial labor (pengelolaan acara komunitas), dan unskilled labor (kampanye voting dan streaming). Penelitian menunjukkan platform X memfasilitasi shipper untuk berpartisipasi aktif dalam budaya partisipatori, menggerakkan ribuan pengikut untuk melakukan tindakan kolektif yang memiliki dampak ekonomis nyata bagi karier idola. Akun @kalewrittings merepresentasikan aktivitas dari fan labor yang baik dengan menggabungkan kreativitas dengan dukungan autentik terhadap idola. Penelitian mengidentifikasi kompleksitas dalam shipping culture di Indonesia, termasuk fenomena fetishisasi, dan pentingnya batasan antara fantasi dan realita. Penelitian ini memberikan kerangka berbasis bukti tentang bagaimana fan labor dalam shipping culture dapat dikelola secara etis dan berkelanjutan tanpa harus merugikan idola.